One-Way Pedestrian Traffic Is a Means of Reducing Personal Encounters in Epidemics - Mello, Bernardo A. (Frontiers in Physics, 2020)
Minimizing social contact is an important tool to reduce the spread of diseases, but harms people's well-being. This and other, more compelling reasons, urge people to walk outside periodically. The present simulation explores how organizing the traffic of pedestrians affects the number of walking or running people passing by each other. By applying certain rules this number can be significantly reduced, thus reducing the contribution of person-to-person contagious to the basic reproductive number, R_0. One example is the traffic of pedestrians on sidewalks. Another is the use of walking or running tracks in parks. It is demonstrated here that the number of people crossing each other can be drastically reduced if one-way traffic is enforced and runners are separated from walkers.